ANALISIS FAKTOR YANG MEMPENGARUHI SOFT SKILLS MAHASISWA DENGAN PROBLEM-BASED LEARNING SEBAGAI VARIABEL INTERVENING (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2023)
This study aims to examine the effect of student organizations and the learning environment on soft skills with problem-based learning as an intervening variable for the Philosophy Study Program students, at Widya Mandira Catholic University. The sampling technique used simple random sampling with the Slovin formula and obtained 57 samples from a total population of 134 students in semesters 3, 5, and 7. This study used primary data from questionnaires and interviews. This study also uses the SEM PLS analysis technique and is processed with Smart PLS software 3.0. The results of the inferential statistical test consist of five hypotheses were accepted and two hypotheses were rejected. Five hypotheses are accepted, namely, student organization variables (X1) and learning environment (X2) have an effect on problem-based learning variables (Y1); learning environment variables (X2) and problem-based learning (X3) have an effect on soft skills variables (Y2); learning environment variables (X2) affect the soft skills variables through the problem-based learning variable as an intermediary variable. While the two hypotheses that were rejected are the direct influence of student organizations (X1) on soft skill variables and also the indirect influence of student organizations on soft skills through problem-based learning variables.